Criteria for the evaluation of indemnity in road accidents: a proposition for judicial policy - Pantoja Echeverri, Marcela; Gómez Cerón, Diego; Ceballos Molano, Raquel; Trujillo Uribe, María (Cuadernos de Administración, 2010)
The road accident, the second cause of violent death in Colombia, is a source of material and moral damages to persons. The norms of civil responsibility oblige the owner of a vehicle or driver to face civil and criminal consequences. The road accident problem and the evaluation of compensation, for material and moral damages, are of great interest due to the number of cases for homicides in traffic accidents in process in criminal courts during long periods in the Cali jurisdiction. In the research made in the Engeneering Statistics School of Valle University a collection of files was done and a survey was made to investigate the judicial policy used to calculate indemnisations in Penal Judgements in the Cali Circuit, where a big disparity in criteria of compensation is noted. Moreover, there is no evidence of using a standard model for evaluating both material and moral damages; also there is no evidence of a top policy in this regard, in the observed sample. Therefore, this study attempts to provide a reference framework for judges and prosecutors to assess the compensation and proposes a model in order to unify criteria for evaluating and fixing the amount of economic compensation to those affected, based on socio-economic characteristics of victims and their heirs. The resulting model proposes criteria used by insurance companies to determine the insurance premiums for life insurance, such as the age and income level of the deceased and their responsabilities to their family.